Pattern of injuries due to wild animal attack among patients presenting to the emergency department: A retrospective observational study - Pradeep Kumar Singh; S Manwar Ali; Rakesh Vadakkethil Radhakrishnan; Chitta Ranjan Mohanty; Manas Ranjan Sahu; Bishnu Prasad Patro; Ijas MS; Susant Kumar Panda (Chinese Journal of Traumatology, 2021)
Purpose: The human-wildlife conflicts (HWCs) causing nuisances and injuries are becoming a growing public health concern over recent years worldwide. We aimed to study the demographic profile, mode of injury, pattern of injury, and outcome of wild animal attack victims presented to the emergency department. Methods: This retrospective cross-sectional study was conducted in the emergency department of a tertiary-care hospital in Eastern India. Data were retrieved from the medical records from May 2017 to May 2021. Patients of all ages and genders attacked by wild animals and secondary injuries were included in this study. Patients with incomplete data, injuries due to the attack of stray and domestic animals and trauma due to other causes were excluded. Demographic profile, mode of injury, the pattern of injury, injury severity score (ISS), radiological pattern, and outcome were recorded. Statistical analysis with R (version 3.6.1.) was conducted. Results: A total of 411 wild animal attack victims were studied, of which 374 (90.9%) were snakebite injuries and 37 (9.1%) were wild mammalian (WM) attack injuries. The mean age of WM attack victims was 46 years, and the male-to-female ratio was 4:1. Elephant attack injury (40.5%) was the most common WM attack injury reported. Most WM attacks (43.2%) occurred between 4:00 a.m. to 8:00 a.m. The median ISS was 18.5 (13–28), where 54.2% of patients had polytrauma (ISS>15). Elephant attack was associated with a higher ISS, but the difference was not significant compared to other animal types (p = 0.2). Blunt trauma was common pattern of injury in the elephant attack injury cases. Lacerations and soft tissue injuries were common patterns in other animal attacks. Among snakebites, neurotoxic was the most common type (55.4%), and lower extremity was the most common site involved. Conclusion: The young male population is the major victim of HWCs; and elephant is the most common animal involved. There is a need to design scientifically sound preventive strategies for HWCs and to strengthen the preparedness in health establishments to manage victims effectively.